Risk Analysis on Leakage Failures of Pipelines Using Hybrid Risk Analysis Method - Daniel Mohammad Rosyid; Bassam Muhammad Drehem; Agro Wisudawan (International Journal of Offshore and Coastal Engineering (IJOCE), 2017)
In this final project has been conducted a study on risk analysis on subsea pipeline leakage by using hybrid risk analysis method. The study begins by determining the scope of the analysis using fault tree analysis which can be determined the main event of the leakage failure of subsea pipeline until the basic event. After determining the scope of the analysis then proceeded to calculate the frequency of each event using the quantitative method. In this calculation is known the frequency of basic event through data from scientific paper programming and scientific research and then calculated the frequency result of top event using Boolean Equation until we get the frequency of failure due to leakage pipelines for 0.0141213. After knowing how big the probability of failure, followed by determining how much impact or consequence of the failure. The consequences of failure are determined based on their impact on safety, environment, and business. In the determination of the impact with the qualitative method using questionnaires interviews to some respondents. After obtaining the result of questionnaire interview then calculated the mean of the questionnaire result to determine how big impact of the failure is based on safety, environment, and business. After knowing how big the probability and consequences of the failure, then determine the position of the risk zone on the risk matrix that refers to DNV RP-G101. After knowing the position of the risk zone, it can be determined how to control risk based on cause-effect.